Human-Computer interaction within the Malaysian university curriculum. - Mahmud, Murni; Hussein, Idyawati; Md Tap, Abu Osman (IIUM Press, 2011)
Human-Computer Interaction (HCI) is considered by the Association for Computing Machinery (ACM) one of the fourteen fundamental areas that represents the body of knowledge of computer science (Calderon, 2009). Due to its multi-disciplinary nature. educators must continue to keep the subject de\-ant to industry and prepare themsel\-es with sufficient principles and methods from each of these contributing disciplines in HCI. This paper describes the status of HCI course. u.hich has been offered in the Malaysian public and pri~tateu niversities. A survey on Malaysian universities' websites was conducted to find out the status of HCI and related course offered by the universities. The finding reveals that HCI courses were offered at different level and faculty \vitIi disparate name at different universities. The subject is offered particularly in computer science; however. there exists other faculty offering HCI to provide foundation wherc relevant